Methodology for Seismic Vulnerability Assessment of Pre-Code Masonry Buildings Using Region-Specific Data - Milkova, Kristina; Dumova-Jovanoska, Elena (Salehan Institute of Higher Education, 2025)
This study presents a comprehensive methodology for evaluating the seismic vulnerability of existing pre-code masonry structures through a multidisciplinary approach that integrates region-specific building typologies with site-specific seismic input. A key gap motivating this work is the absence of fragility curves for masonry structures typical of the region despite their prevalence and high seismic exposure. Recognizing the importance of reliable Seismic Hazard Assessment (SHA) in risk evaluation, a scenario-based Neo-Deterministic Seismic Hazard Assessment (NDSHA) approach was employed. This method incorporates a detailed understanding of the region’s tectonic regime, active fault systems, earth crust structure, and historical seismicity to produce realistic site-specific response spectra for analysis. The seismic capacity of the structures was assessed using multiple iterations of a nonlinear static (pushover) analysis, accounting for uncertainties in the material and geometric input parameters. The structural displacement was used as the primary damage index, and the damage was classified into five discrete damage grades. Consequently, new fragility and reliability curves were developed: (i) a general set for unreinforced masonry (URM) structures, (ii) four regional sets corresponding to distinct zones within the country, and (iii) two sets differentiating between regular and irregular plan configurations. The novelty of this study lies in the development of region-specific fragility curves for URM buildings, providing urgently needed tools for seismic risk assessment and supporting mitigation strategies and decision-making at the local and national levels.